2021
DOI: 10.2147/dddt.s321824
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Anticancer Activity of a Novel Phenolic Compound from Garcinia porrecta Against the MCF-7 Breast Cancer Cell Line in vitro and in silico

Abstract: Background Cancer is a leading cause of death worldwide, with breast cancer being the most common invasive cancer type in women. Several therapeutic strategies have been explored to reduce the mortality rates of breast cancer. Chemotherapy is the most commonly used systemic treatment, but associated with numerous side-effects. Development of anticancer agents with high efficacy and minimal negative effects is therefore an important focus of research. Natural materials provide an excellent source o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Polyphenols occupy an important place in the life of plants by intervening in their metabolism. There are known about 8.000 plant-derived polyphenol compounds with antioxidant and antitumor properties [53][54][55][56][57][58]. Polyphenols are organic, watersoluble compounds that contain in their molecule one or more aromatic rings with one or more hydroxyl groups.…”
Section: Polyphenols -Chemical Structure and Classificationmentioning
confidence: 99%
“…Polyphenols occupy an important place in the life of plants by intervening in their metabolism. There are known about 8.000 plant-derived polyphenol compounds with antioxidant and antitumor properties [53][54][55][56][57][58]. Polyphenols are organic, watersoluble compounds that contain in their molecule one or more aromatic rings with one or more hydroxyl groups.…”
Section: Polyphenols -Chemical Structure and Classificationmentioning
confidence: 99%
“…Doxorubicin was used to check the sensitivity of MCF-7 and T47D cell lines, where doxorubicin and NK immunotherapy in combination supported the BC treatment [11]. Further, a research study evaluated effect of phenolic compound on MCF7 cell line and showed that used compound has anti-cancer potential [12]. Trilla-Fuertens and his team in 2018 used CAMA1, T47D, MCF7, MDA-MB-468, HCC1143 and MDA-MB-231 cell lines in order to check metabolic drug response using metformin and rapamycin [13].…”
Section: Breast Cancer Cell Linesmentioning
confidence: 99%
“…The MCF‐7 cancer cell line has complex morphological and molecular characteristics. One of the reasons for the widespread use of the MCF‐7 cell line in laboratories around the world is its identification as an advantageous cancer model due to its known cytological and molecular characteristics [2–4] …”
Section: Introductionmentioning
confidence: 99%
“…One of the reasons for the widespread use of the MCF-7 cell line in laboratories around the world is its identification as an advantageous cancer model due to its known cytological and molecular characteristics. [2][3][4] Breast epithelial cell homeostasis requires the balance of cell proliferation with apoptosis. Cancer cells treated with anti-cancer compounds usually loss their viability using apoptotic pathways.…”
Section: Introductionmentioning
confidence: 99%